2010
DOI: 10.1007/s00210-010-0581-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of host cell chaperones/PPIases during cellular up-take of bacterial ADP-ribosylating toxins as basis for novel pharmacological strategies to protect mammalian cells against these virulence factors

Abstract: Bacterial exotoxins exploit protein transport pathways of their mammalian target cells to deliver their enzymatic active moieties into the cytosol. There, they modify their specific substrate molecules resulting in cell damage and the clinical symptoms characteristic for each individual toxin. We have investigated the cellular uptake of the binary actin ADP-ribosylating C2 toxin from Clostridium botulinum and the binary lethal toxin from Bacillus anthracis, a metalloprotease. Both toxins are composed of a bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 100 publications
0
30
0
Order By: Relevance
“…First, the B components bind to their cell receptors and serve as docking platforms for the A components. After receptor-mediated uptake of the AB-complexes, the B components form pores in the membranes of endosomal vesicles that serve as translocation channels for the A components to traverse from the endosomal lumen into the cytosol (for review, see [65,66,106]). Translocation of A components for the C2 and iotalike toxins is facilitated by the activities of particular host cell chaperones, such as Hsp90 [107,108] (for a review of Hsp90, see [109]), and folding helper enzymes, including peptidyl-prolyl cis/trans isomerases (PPIases) including cyclophilins (Cyp) [110,111] and FK506 binding proteins (FKBPs) [112], as depicted in Figure 14.8.…”
Section: Cellular Uptake Of Binary Actin Adp-ribosylating Toxins Is Fmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the B components bind to their cell receptors and serve as docking platforms for the A components. After receptor-mediated uptake of the AB-complexes, the B components form pores in the membranes of endosomal vesicles that serve as translocation channels for the A components to traverse from the endosomal lumen into the cytosol (for review, see [65,66,106]). Translocation of A components for the C2 and iotalike toxins is facilitated by the activities of particular host cell chaperones, such as Hsp90 [107,108] (for a review of Hsp90, see [109]), and folding helper enzymes, including peptidyl-prolyl cis/trans isomerases (PPIases) including cyclophilins (Cyp) [110,111] and FK506 binding proteins (FKBPs) [112], as depicted in Figure 14.8.…”
Section: Cellular Uptake Of Binary Actin Adp-ribosylating Toxins Is Fmentioning
confidence: 99%
“…This substance, which acts on the molecular level of toxin uptake into cells, could be considered as a lead compound for developing novel therapeutic strategies against not only binary actin ADP-ribosylating toxins (e.g., food poisoning), but also during infections that include hypervirulent strains of C. difficile. Here, such inhibitors should also work as adjunct therapies against bacteria, already resistant against many traditional antibiotics (for review, see [106]). …”
Section: Cellular Uptake Of Binary Actin Adp-ribosylating Toxins Is Fmentioning
confidence: 99%
“…Some AB toxins have an intrinsic pore-forming capacity that is triggered by the low pH of the acidified endosomes. The B subunits of these toxins undergo acid-induced conformational changes which embed the B subunit in the endosomal membrane, forming a protein-conducting channel that subsequently allows A chain egress to the cytosol [1,2,3]. Other AB toxins have no pore-forming capacity and must therefore utilize an existing protein-conducting channel in the host endomembrane system for A chain passage to the cytosol.…”
Section: Ab Protein Toxinsmentioning
confidence: 99%
“…Like diphtheria toxin, passage through a low pH compartment and unfolding of the C. botulinum C2 toxin catalytic domain are pre-requisites for entry (Barth et al, 2011). In the case of the C. botulinum C2 toxins, Haug et al (2003) clearly demonstrated that Hsp 90 ATPase activity was not acting as an allosteric regulator of v-ATPase, and ruled out the possibility that Hsp 90 inhibition resulted in the enhanced proteosomal degradation of toxin.…”
Section: Hsp 90 Functions As a Ctfmentioning
confidence: 99%
“…All of the bacterial protein toxins requiring Hsp 90 for cytosolic entry that have been identified to date are ADP-ribosyltransferases, and Barth (2011) has hypothesized that there is some conserved component of the ADP-ribosyltransferase domain that mediates interaction with Hsp 90, either directly or indirectly through an adaptor protein or co-chaperone.…”
Section: Hsp 90 Functions As a Ctfmentioning
confidence: 99%